Scholarship-friendly publishing - Sally, Morris (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
Publishers are making great efforts to find out what their customers - authors, readers and librarians - need, and their publishing practices are changing in response to what they hear. Much has already been achieved in making more content available to more people (for not much more money) and in adopting more liberal licensing policies towards both authors and users. Alternative publishing models, such as Open Access, are of great interest to publishers but present difficult economic challenges which need to be carefully investigated if we are not to throw the baby out with the bathwater.